1975
DOI: 10.1577/1548-8659(1975)104<296:ecopsi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Culture of Penaeid Shrimp in Louisiana Salt-marsh Impoundments

Abstract: Wild and hatchery‐produced shrimp were stocked in two impoundments off Bayou Jean Lacroix in 1968 and 1969. Maximum annual harvest was 141.2 kg/hectare of wild shrimp averaging 119 mm in total length (73 count per kg, heads on) from an impoundment in which attempts were made to remove predators and competitors. Harvest in an impoundment in which predators and competitors were not removed was 48.2, 79.1, and 161.9 kg/hectare of wild shrimp, blue crabs, and large fishes, respectively. Lack of predator control re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Brown shrimp emigration from both weired and unweired ponds was correlated with new and full moons, even though emigration from the weired pond was delayed. This lunar relationship has also been noted during other brown shrimp emigration studies (Copeland 1965;King 1971;Rose et al 1975;Knudsen 1986), although Copeland (1965) concluded that emigration peaked only during the full moon and King (1971) concluded that it peaked only during the new moon.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Brown shrimp emigration from both weired and unweired ponds was correlated with new and full moons, even though emigration from the weired pond was delayed. This lunar relationship has also been noted during other brown shrimp emigration studies (Copeland 1965;King 1971;Rose et al 1975;Knudsen 1986), although Copeland (1965) concluded that emigration peaked only during the full moon and King (1971) concluded that it peaked only during the new moon.…”
Section: Discussionsupporting
confidence: 66%
“…Some aspects of brown shrimp ecology in Louisiana and Texas inshore waters have been studied extensively (see review by Zein-Eldin and Renaud 1986). In addition, several researchers have concentrated on juvenile brown shrimp ecology in the shallowest water of interior salt and brackish marshes (Herke 1971;Rose et al 1975;Knudsen et al 1977;Perry 1981;Zimmerman and Minello 1984;Knudsen et al 1985;Herke et al 1987c). Some of this research occurred in areas influenced by weirs.…”
mentioning
confidence: 99%
“…The growth rates, γ i , were assumed to be constant within each stage and based on field studies [ 21 ]. We divided growth rates by the stage size ranges, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…See van de Kerk et al (2016) for a full explanation of stage-class generalizations and underlying assumptions. Growth rates were derived from published field-based studies and were assumed constant within a class; the growth rate was estimated at 30 mm/month for settlers and 11.55 mm/month for recruits (Rose et al 1975;Lassuy 1983). As in van de Kerk et al (2016), growth rates γ i i ¼ S; R; A ð Þwere divided by published size ranges (Lassuy 1983) to calculate transition rates between life stages α i (equation 1).…”
Section: Life History Modelmentioning
confidence: 99%